MUHAMMAD RAHIMKHON II – ENLIGHTENED RULER AND POET - Uktamov Tohirjon Gayrat ugli (Web of Journals Publishing, 2024)
This article provides information about Sayed Muhammad Rahim Khan Soniy, one of the major Khans of the qongot dynasty, who ruled the Khiva Khanate by the author. The events of his reign in the Khiva Khanate are considered.
Keywords: Eltuzar, Muhammad Rahim Khan Soniy, Feruz, Said Muhammad Khan, Khudoybergan muhrkan, Ogahiy, Bobojan Torah.